Chondrogenic pre-induction of human mesenchymal stem cells on β-TCP: Enhanced bone quality by endochondral heterotopic bone formation - Janicki, Patricia; Kasten, Philip; Kleinschmidt, Kerstin; Luginbuehl, Reto; Richter, Wiltrud (Acta biomaterialia, 2010)
New techniques to heal bone defects include the combination of bone substitute materials with mesenchymal stem cells (MSC). To find solutions not hampered by low material resorbability or high donor variability of human MSC, the potency of such composites is usually evaluated by heterotopic bone formation assays in immunocompromised animals. The aim of this study was to investigate whether resorbable phase-pure β-tricalcium-phosphate (β-TCP) could support heterotopic bone formation by MSC comparable to partially resorbable hydroxyapatite/tricalcium-phosphate (HA/TCP). Furthermore, in light of disappointing results with osteogenic in vitro priming of MSC, we tested whether chondrogenic pre-induction of constructs may allow for enhanced bone formation by triggering the endochondral pathway. β-TCP granules of three different sizes and HA/TCP were seeded with MSC and transplanted subcutaneously into immunocompromised mice either immediately or after a chondrogenic pre-induction for 6weeks. After 8weeks, explants were analysed by histology. β-TCP seeded with unprimed MSC revealed intramembranous bone formation without haematopoietic marrow with 3.8-fold more bone formed with granules smaller than 0.7mm than with 0.7-1.4mm particles (p⩽0.018). Chondrogenic pre-induction of β-TCP/MSC composites resulted in collagen type II and proteoglycan-rich cartilage-like tissue which, after transplantation, underwent endochondral ossification, yielding ectopic bone produced by human cells while haematopoietic marrow was derived from the mouse. Transdifferentiation of MSC-derived chondrocytes to osteoblasts or direct osteogenesis of cartilage-resident MSC is postulated to explain the human origin of new bone. In conclusion, β-TCP was significantly more osteo-permissive (p=0.004) than HA/TCP for human MSC, and chondrogenic priming of β-TCP/MSC represented a superior approach capable of supporting full bone formation, including marrow organization.